Job Readiness Level to Address 4.0 Skills: An Empirical Study on TVET Students in Electrical and Electronics Field - Wong, Goon Shek; Abdullah, Nurhanim Saadah (Journal of Technical Education and Training, 2025)
Malaysia has developed TVET programs to nurture a skilled workforce for its industrial sector. Many graduates face challenges in job readiness, impacting their employability in today’s evolving technological environment. Outdated skills pose obstacles, potentially leading to unemployment or reduced workplace performance. This study determined the job readiness level of final-year TVET students in the Electrical and Electronics fields across the Malaysia Technical University Network (MTUN), focusing on Industry 4.0 skills. Using a quantitative, descriptive research design and surveys, the study identified essential Industry 4.0 skills using an IR 4.0 skills checklist, evaluated the current job readiness level of final-year TVET students in the Electrical and Electronics fields at MTUN using a job readiness questionnaire, and identified the differences in job readiness levels across MTUN universities. Stratified sampling and simple random sampling techniques were applied in this research. There are 11 IR 4.0 skills considered essential for job readiness in the Electrical and Electronics field from the industry perspective. The ranking of the 11 skills, from top to bottom, is as follows: technical knowledge, reasoning and problem-solving, analytical thinking and technological literacy, big data analytics, communication skills, artificial intelligence, leadership and social influence, curiosity and lifelong learning, quality control, and critical thinking, under the dimensions of People, Process, and Technology. The job readiness level of final-year TVET undergraduate students in the Electrical and Electronics (E&E) field at the MTUN was 3.61, which falls under the category of approaching readiness. The significance value of the Kruskal-Wallis test was 0.012, which is less than 0.05. A statistically significant difference was found in the job readiness levels of final-year TVET undergraduate students in the Electrical and Electronics (E&E) field across the MTUN. UTHM’s overall mean is higher than those of the other three universities.